Biofilm layers affect the treatment outcomes of NaF and Nano-hydroxyapatite - Zhang, M; He, L B; Exterkate, R A M; Cheng, L; Li, J Y; Ten Cate, J M; Crielaard, W; Deng, D M (Journal of dental research, 2015)
During caries formation, dental biofilms function not only as acid producers but also as reservoirs and diffusion barriers for active caries-preventive components. The aim of this study was to investigate the influence of biofilms as a stagnant layer on the efficacy of NaF and nano-hydroxyapatite (nHA). Biofilms of Streptococcus mutans C180-2 were formed on the surfaces of artificially demineralized enamel in an active attachment biofilm model. After 2 days of biofilm formation, the model was subjected to a pH-cycling schedule, together with a control group without biofilms. Specimens were treated for 5 min twice daily with water, a 10% nHA slurry, or 18.4 mM NaF. At the end of the pH-cycling period, the biofilms were removed for the determination of the viable counts, the lactic acid production, and the calcium content. The mineral changes in the demineralized enamel blocks were analyzed by transversal microradiography. No differences in the biofilm viable counts and lactic acid production were found in the different treatment groups. The mean calcium content of the biofilms in the nHA group was 60.7 ± 15.3 mmol/g wet weight, which was approximately 8-fold higher than in the other 2 groups. The application of NaF resulted in net remineralization, but in the presence of a biofilm, net demineralization was observed. In contrast, nHA treatment reduced further demineralization compared with the water treatment, but the presence of a biofilm enhanced this effect. In conclusion, the presence of biofilms clearly influenced the treatment outcomes of anticaries products. Biofilms could either enhance or impede their efficacy. This result implies that biofilms should be included in the in vitro tests for the preclinical screening of caries-protective agents.